Comparative bone identification human subadult to nonhuman - France, Diane L. (CRC Press, Taylor & Francis Group, 2017)
This book presents new images of human bones representing many states of maturation from neonate to 20 years old. It also extends the scope of the former work by focusing on the smaller bones of fetuses and young humans and comparing them to bones of birds, reptiles, marine mammals, fish, and a frog that may be confused with those of a subadult human.